2011
DOI: 10.1167/iovs.11-7479
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Transcriptome Analysis of Human Retina-Derived Cell Lines ARPE-19 and Y79 Using the Vector-Capping Method

Abstract: PURPOSE. To collect an entire set of full-length cDNA clones derived from human retina-derived cell lines and to identify full-length transcripts for retinal preferentially expressed genes. METHODS. The full-length cDNA libraries were constructed from a retinoblastoma cell line, Y79, and a retinal pigment epithelium cell line, ARPE-19, using the vector-capping method, which generates a genuine full-length cDNA. By single-pass sequencing of the 5'-end of cDNA clones and subsequent mapping to the human genome, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…chr7:9310980–9331512 is on 7p21, and is at the intergenic region near a noncoding gene RBSG3 (retinoblastoma‐specific gene 3). The sequences of this gene were derived only from retinoblastoma . Bookstein et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chr7:9310980–9331512 is on 7p21, and is at the intergenic region near a noncoding gene RBSG3 (retinoblastoma‐specific gene 3). The sequences of this gene were derived only from retinoblastoma . Bookstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of this gene were derived only from retinoblastoma. 36 Bookstein et al confirmed the existence of retinoblastoma mutations in some human prostate carcinomas. 37 And the retinoblastoma tumor suppressor gene is functionally inactivated in a broad range of both paediatric and adult cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that human retinoblastoma Y79 expressed three variants of the EYS gene, including a long full-length cDNA clone with 7989 bp encoding a short form of EYS with 594 amino acids, but were not able to obtain the full-length cDNA clone encoding the longest form of EYS. 25 Thus, there seem to be many forms of EYS variants, including unknown ones. Given that the short EYS variants contain the N-terminal EGF domains identical to those of the long form, these variants may partially compensate for the loss of the long form of EYS.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq library preparation methods that provide uniform, full-length sequence coverage of expressed transcripts are particularly useful when characterizing transcription start sites, 31 5′-/3′-untranslated regions, 32 , 33 splicing variants, 34 , 35 operon organization 36 and pathogen transcriptomes 37 - 39 . Thus, in evaluating the performance of Peregrine library preparation it was important to characterize the sequencing coverage provided in terms of its distribution along the length of individual transcripts.…”
Section: Resultsmentioning
confidence: 99%